Additions to the Genus Bactris (Arecaceae)of Mesoamerica - Cascante Marín, Alfredo (2000)
Two new endemic species of Bactris, found in the understorey of humid forest on the Pacific Coast of Costa Rica, are described and illustrated. Bactris ana-juliae is 1.8-3.0 m tall, and B. herrerana is 2.0-3.0 m tall.